Hemodynamics in a curved artery with mild stenosis: A two-layered model - Pushpa Nidhi Gautam; Chudamani Pokharel; Tuk Bahadur Rana; Jeevan Kafle (International Journal of Thermofluids)
Arterial stenosis is the leading cause of cardiovascular disease and significantly contributes to premature death worldwide, which indicates the need for deeper research into its dynamics. This abnormal narrowing of the arterial lumen affects hemodynamics, and more effect is seen if the curvature is also present at the same location. Because the materials, flow patterns, and thickness are different in the core and peripheral layer of the artery, a two-layered model can address the situation correctly. A new model is developed in this work after incorporating a quadratic curvature term in conservative form in the Navier–Stokes equation. The equation is then solved to get analytical solutions for the flow parameters in a curved stenotic region of an artery and the results are analyzed. The velocity profile, volumetric flow rate, pressure gradient and shear stress decrease due to curvature and effect of curvature is less for more viscous fluid. The result obtained is more appropriate and realistic than in the one-layer model. This model helps to understand the blood flow system in cardiovascular arteries with mild stenosis before reaching the pathological conditions, and many lives can be saved.